Los delirios: un yacimiento hidrotermal de oro y plata en la región de Vetas, Santander (Colombia) (2003)
Los Delirios Au-Ag deposits is located 700 meters northwestern of Vetas city (Departamento de Santander) and consists of quartz-sulfide-oxides veins that cuts quartz-feldspar bearing biotite gneisses from Bucaramanga Gneiss Formation. Three vein systems are determinated:(1) N30-45°W dips 25-40°NW; (2) N10°W dips 60-70°SW; (3) N70°W dips 70°SW o 60°NE. The vein thickness is between 0.45 and 2.0 meters. The veins have a gray color and massive to brecciated and cavernous structures. The ore mineralogy consists in gold, silver, pyrite, chalcopyrite, pyrrhotite, galena, bornite, calcosine, marcasite, covelline, tetrahedrite, ilmenite, magnetite, hematite. Gange minerals are mainly quartz and plagioclase. The alteration of the deposits is phyllic. The gold and silver contents are 0.5-2.0 gr/T y 0.0-6.48 gr/T respectively. Ore mineralogy, wall alteration and dominant Au-Ag-Pb mineralization in the deposits are like epithermal low-sulfidation or adularia-sericite systems.